1990
DOI: 10.1128/mcb.10.1.28
|View full text |Cite
|
Sign up to set email alerts
|

The product of the H19 gene may function as an RNA.

Abstract: The mouse H19 gene was identified as an abundant hepatic fetal-specific mRNA under the transcriptional control of a trans-acting locus termed raf. The For the majority of cloned eucaryotic genes, their protein products were already known prior to cloning. More recently, differential hybridization screens of cDNA libraries have been used to clone genes with specific tissue and temporal patterns of expression, without regard to their products. The murine H19 gene is such a gene. It was originally identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
579
2
9

Year Published

1996
1996
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 926 publications
(597 citation statements)
references
References 35 publications
7
579
2
9
Order By: Relevance
“…H19 RNA appears as 2.3 kb band corresponding to the sum of the ®ve exons of the H19 gene (Brannan et al, 1990). In the majority of the blots done by us and others a second band of approximately 4 kb is visible.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…H19 RNA appears as 2.3 kb band corresponding to the sum of the ®ve exons of the H19 gene (Brannan et al, 1990). In the majority of the blots done by us and others a second band of approximately 4 kb is visible.…”
Section: Resultsmentioning
confidence: 77%
“…It is bound in 28S cytoplasmic RNPs and not to ribosomes (Brannan et al, 1990). Its function is enigmatic.…”
Section: Introductionmentioning
confidence: 99%
“…Genes involved in the regulation of cell proliferation, such as IFI16, h19 and RCC1, but also hox2 (Acampora et al, 1989;Brannan et al, 1990;Bischoff and Ponstingl 1991;Trapani et al, 1994), were found to be preferentially expressed in sensitive cell lines. Intriguingly, genes encoding SHB and PKC-ζ proteins, known components of defined signal transduction pathways (Barbee et al, 1993;Welsh et al, 1994), appear to be preferentially expressed in IFN-α resistant cells (Figure 4, panels A and B).…”
Section: Discussionmentioning
confidence: 99%
“…2 of them, IFI16 and RCC1 encode nuclear proteins endowed with mitotic regulation and transcriptional activation capacities, respectively (Bischoff and Ponstingl, 1991;Trapani et al, 1994). A third is the hox2 homeobox gene (Acampora et al, 1989), whereas the fourth, h19 gene, encodes an untranslated RNA, involved in the DNA methylation and genetic imprinting processes (Brannan et al, 1990). Notably, however, RCC1 gene was not expressed in one IFN-α sensitive cell line (ME51).…”
Section: Detection Of Potential Marker Genes For Ifn-α α Responsivenessmentioning
confidence: 99%
“…Whereas IGF2 produces a growth factor in both mouse and man (Stewart and Rotwein, 1996), the function of H19 is enigmatic. In the mouse, sequences¯anking H19 control the activity of Igf2 in cis while the structural gene has no documented function in trans (Brannan et al, 1990;Leighton et al, 1995).…”
Section: Introductionmentioning
confidence: 99%